Of art and of land - Fentz, Christine (Peripeti, 2022)
A presentation of the performing artwork of Secret Hotel and the work of Earthwise Residency – both entities work with the more-than-human, and therefore with an innate sustainable set of values. This also applies to the biannual interdisciplinary symposium Earthbound, which is also presented.